Manajemen Implementasi Program Literasi Numerasi Berbasis Matific dan Dampaknya terhadap Hasil Belajar Peserta: Studi Mixed Methods - Zahirotul Kamiliyah; Roizatul Faruk (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2026)
This study was motivated by the low levels of numeracy literacy among students and the increasing use of digital technology as an alternative learning solution. However, the effectiveness of technology-based programs depends heavily on how they are managed, particularly when dealing with vulnerable groups facing limited digital access. This study aims to analyze the implementation management of the Matific app-based numeracy literacy program and its impact on student learning outcomes. The central research questions concern whether the implemented program significantly improves learning outcomes and how the implementation process unfolds in the field. A mixed-methods approach with an explanatory sequential design was employed. Quantitative data were derived from pre-test and post-test results, while qualitative data were gathered through observations and interviews. The study sample consisted of 55 students from a social welfare institution (LKSA) in Puncu District, Kediri. The results indicate an increase in the average score from 48.37 to 53.26; however, this increase was not statistically significant (p = 0.066). Qualitative findings reveal that the program's implementation was influenced by limited facilities, restricted access to technology, and the varying ability levels of the students.